Delineation of the Genetic Architecture and Clinical Polymorphism of 3q29 Duplication Syndrome: A Review of the Literature and a Report of Two Novel Patients With Single‐Gene BDH1 Duplications - A. A. Kashevarova; M. E. Lopatkina; O. Yu. Vasilyeva; D. A. Fedotov; A. D. Lobanov; E. A. Fonova; I. Z. Zhalsanova; A. A. Zarubin; O. A. Salyukova; E. O. Belyaeva; V. V. Petrova; E. G. Ravzhaeva; et al. (Molecular Genetics & Genomic Medicine)
ABSTRACT Background Chromosome 3q29 duplication syndrome is a rare chromosomal disorder with a frequency of 1:5000 in patients with a neurodevelopmental phenotype. The syndrome is characterized by phenotypic polymorphism and reduced penetrance. Methods Patients were investigated by performing a cytogenetic analysis of GTG‐banded metaphases, aCGH with the SurePrint G3 Human CGH Microarray 8×60K, qPCR, FISH, and WES. Results Here, we report five new patients with atypical duplications overlapping with the 3q29 duplication syndrome region and no other genetic findings. In two patients, duplications were found in the single BDH1 gene, a candidate gene for the 3q29 duplication phenotype. For the first time, we delineated and described the smallest minimal critical region, including the single BDH1 gene; in our patients, this region was associated with ASD, heart defects, biliary tract dysfunction, and obesity. The frequencies of the pathological phenotypes in duplication carriers reported in the literature were calculated and compared with those in patients with 3q29 deletions. Most of the phenotypes were observed in both groups but were significantly less common among individuals with 3q29 duplications. Mirrored phenotypes in patients with duplications and deletions included overweight and weight deficit. Schizophrenia, generalized anxiety disorder, and recurrent ear infections were unique phenotypes of patients carrying deletions. Conclusion Chromosome 3q29 duplication syndrome is characterized by a complex genetic architecture and clinical polymorphism.